Barriers and facilitators to a combined strategy of HPV vaccination and cervical cancer screening among Mexican women - Leith León-Maldonado; Alejandra Cabral; Gabriela Pages; Brandon Brown; Betania Allen-Leigh; Eduardo Lazcano-Ponce; Francesc Xavier Bosch; Donna Spiegelman; Leticia Torres-Ibarra; Raúl U. Hernández-Ramírez; Emilie Egger; Berenice Rivera-Paredez; et al. (Human Vaccines & Immunotherapeutics)
HPV-FASTER is an innovative public health intervention combining HPV vaccination and HPV-based screening in adult women at the same visit. FASTER-Tlalpan adapted the combined HPV-FASTER strategy in Tlalpan, Mexico City for women aged 25–45 years. To understand the barriers and facilitators to participation in a combined strategy, we conducted semi-structured interviews with 14 FASTER-Tlalpan participants. We used the constant comparative method for the analysis, as well as the socioecological model to organize the findings. At the intrapersonal level, barriers included the belief that only younger women are at risk for HPV, embarrassment about the pelvic exam, and lack of time, while facilitators were having information regarding the benefit of the combined strategy, perception of time saved by having both procedures at once, feeling reassured about their health, self-esteem regarding their health, and perceived severity of cervical cancer. Interpersonal-level barriers were experiences of stigma and prejudice, and lack of support from partners, while facilitators were family encouragement and peer-to-peer communications. Institutional-level barriers were lack of infrastructure and inconvenient hours at the health center, perceived high time burden, and low quality of care from providers, while facilitators included high-quality care by health center personnel, including partners in the combined strategy, and phone reminders. Community-level facilitators included willingness to participate. Public policy facilitators included mass information campaigns and free procedures. Our findings point to significant barriers which need to be addressed, along with facilitators which can be leveraged to scale up the combined strategy in similar settings.